Analisis Jaring Aspirasi Melaui Reses Dewan Perwakilan Rakyat Daerah Lombok Timur Tahun 2015 - Hidayatullah Hidayatullah; Ulung Pribadi (Journal of Governance and Public Policy, 2016)
Any people who live in democracies have the right to participate in development daerah. Salah of his formthrough aspiration of activities DPRD. Pelaksanaan recess recess East Lombok Regency spotlight for masyarakat.Mekanisme recess that rarely publicized causes irregularities occurring mainly in the division budget item recess,the process of implementation and poor implementation accommodate the aspirations masyarakat. sehinggamasyarakatpun not feel the results of that activity. This study discusses the mechanism and the results of theactivities during the recess which is at the level of implementation of a technical nature and the result was neverrealized. In this study, the method used is qualitative analysis method in a descriptive way. The data in this studywere obtained through interviews and research shows that the first dokumentasi. Hasil; the implementationprocess is done by a recess for Parliament East Lombok is quite varied ranging from formal activity as carried outat the village office until iformal activities like sitting at home-rumah. Kedua discussion; The results of the publicreported a net aspirations and reported on the internal fractions by weighing the priority scale that later becamecommon view on a fraction of the plenary session. Third: deliberation undertaken Parliament in following up theresults of the recess rare word consensus so that the fraction of lobbying by local governments, sesameParliament and sesame fraks, i nevertheless the realization of aspirations were never perceived by the publicbecause too much importance to the local government and legislative.